FORMATION OF AN INTERNATIONAL IMAGE: A COMPARATIVE ANALYSIS OF THE EXPERIENCE OF GERMANY AND UZBEKISTAN (British Journal of Global Ecology and Sustainable Development, 2023)
The subject of the research is the formation of a correct and positive image of the country abroad. The authors consider in detail the experience of Germany and Uzbekistan in building an international image, comparing the strategies of these countries. At the same time, the components of the strategies are analyzed, in particular, the application of the concept of the concept of "soft power", which makes the increase in the country's influence in the world dependent on the attractiveness of the country. The authors pay special attention to the extent to which countries manage to achieve their goals in the process of forming an international political image, and what restrictions may arise in this case. During the study, a systematic approach was used, as well as such methods of scientific knowledge as analysis, synthesis, induction, deduction, comparison, and historical method. In conclusion, the authors come to the conclusion that in the formation of the international image, Germany relies on economic development. At the same time, Uzbekistan is positioning itself as a strong state, including by converting "hard" power into "soft" power. To enhance the international image, both countries use the institutions of "soft power". At the same time, it is noted that the achievement of foreign policy goals through the formation of the image is hindered by the fears of EU neighbors for Germany, the lack of elaboration of a strategy for shaping the image abroad and domestic problems for Uzbekistan.